Evaluation of cold atmospheric pressure plasma effects on Pseudomonas aeruginosa wound infection in a mouse model - Reyhaneh Shekari; Gholamreza Zarrini; Vahid Siahpoush; Farzam Sheikhzadeh Hesari (Iranian Journal of Microbiology)
Background and Objectives: Antibiotic resistance in microorganisms is a significant global health concern. Cold atmospheric plasma is an innovative and promising method for inactivating bacteria. This study aimed to evaluate the effects of cold plasma on Pseudomonas aeruginosa in a mouse wound infection model. Materials and Methods: The disk diffusion method was used to perform antibiograms after isolating the bacteria. A multidrug-resistant strain was then selected. The bactericidal activity of cold helium plasma was investigated in vitro. The optimal cold plasma conditions were determined in the laboratory, with a flow of 3 liters per minute and a power of 1.1 watts. These conditions were later used for in vivo evaluations. Results: In a laboratory study, helium gas plasma treatment for 8 minutes reduced P. aeruginosa by 2.5 logs. In the in vivo study, plasma reduced the wound's microbial load in mice by 1.9 log. The antibiotic treatment group had a 1.2 log reduction. Both plasma and antibiotic therapies had similar effects on microbial inactivation. Conclusion: The overall evaluation of wound healing time and pathological features showed that plasma was generally better than antibiotic treatment. Plasma can inactivate P. aeruginosa in wounds and accelerate wound healing.